Legal Protection for Digital Platform Workers: A Legal Analysis of Partnership Relations from the Perspective of Employment Law in Indonesia - Guvo Deswarth Purba; Nia Amira (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
The rapid development of the digital economy in Indonesia has given rise to a new work model through digital platforms that bases employment relationships on the concept of partnership. However, this model creates legal ambiguity due to the weak bargaining position of platform workers and the existence of elements of employment relationships that are factually fulfilled but formally omitted. This study aims to analyze legal protection for digital platform workers and review the status of partnership relationships from the perspective of labor law in Indonesia, particularly after the implementation of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into law.